STUDI KETAHANAN PANGAN PADA RUMAHTANGGA MISKIN DAN TIDAK MISKIN - Sukandar, Dadang; Khomsan, Ali; R, Hadi; Anwar, Faisal; S, Eddy (GIZI INDONESIA, 2006)
Food security at household level refers to the ability to ensure an adequate intake of food for the whole family members. Food security includes physical (food availability), economical (purchasing power), nutritional (fulfilled individual need of adequate nutrient), cultural and religious aspects, health, and time. The objective of this study was to identify factors affecting food security of the households. The study was conducted in a highland area of Bogor District and a coastal area of Indramayu District, West Java, Indonesia. In Bogor, 375 samples and in Indramayu 376 samples were selected randomly. The data collected through questionnaires were tried out before hand so that they were more operational. The revised questionnaires and forms then were used by the enumerators. Food security reflected by the sufficiency level of energy and protein intake shows that in general poor households have a low level of nutritional. Households in Indramayu have a higher food security than those in Bogor (particularly in terms of protein sufficiency). Factors having a significant association on food security of households were the number of household members, husband ages, and household category. The number of members in households affect significantly the energy sufficiency level. The number of members in households, husbands’ ages, and household category have a significant effect on the level of protein sufficiency.Key words: food security, energy sufficiency, protein sufficiency.